The Effect of Asset Structure, Bank Size, Profitability, Bank Growth, and Liquidity on Capital Structure of Islamic Banking in Indonesia - Cut Sara Dara Meutia; Faisal; A. Sakir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates how different factors such as asset structure, bank size, profitability, bank growth, and liquidity affect the capital structure of Islamic (Sharia) banking in Indonesia. The study focuses on Sharia banks listed on the Indonesian Stock Exchange (BEI) and analyzes data from 3 selected companies using purposive sampling and their monthly reports. The research uses Structural Equation Modeling (SEM) with the SmartPLS program for data analysis. The findings show that asset structure and profitability have a significant impact on the capital structure, while bank size, bank growth, and liquidity do not. The results also reveal that asset structure affects capital structure positively, where an increase in asset structure will also increase capital structure, while profitability affects capital structure negatively, where an increase in profitability will decrease capital structure